Association Between Ischemic Optic Neuropathy and Inflammatory Bowel Disease: A Population-Based Cohort Study in Taiwan - Lin, Ting-Yi; Lai, Yi-Fen; Chen, Po-Huang; Chung, Chi-Hsiang; Chen, Ching-Long; Chen, Yi-Hao; Chen, Jiann-Torng; Kuo, Po-Chen; Chien, Wu-Chien; Hsieh, Yun-Hsiu (Frontiers in Medicine, 2021)
Abstract Background: Ischemic optic neuropathy (ION) is a possible extraintestinal manifestation of inflammatory bowel disease (IBD). We investigate the relation between IBD and ION and possible risk factors associated with their incidence. Methods: Medical records were extracted from the National Health Insurance Research Database from January 1, 2000, to December 31, 2013. The main outcome was ION development. Univariate and multivariate Cox regression analyses were performed. Results: We enrolled 22,540 individuals (4,508 with IBD, 18,032 without). The cumulative risk of developing ION was significantly greater for patients with IBD versus patients without (Kaplan–Meier survival curve, p = 0.009; log-rank test). Seven (5%) and five (0.03%) patients developed ION in the IBD and control groups, respectively. Patients with IBD were significantly more likely to develop ION than those without IBD (adjusted hazard ratio = 4.135; 95% confidence interval: 1.312–11.246, p = 0.01). Possible risk factors of ION development were age 30–39 years, diabetes mellitus, hypertension, ischemic heart disease, atherosclerosis, and higher Charlson comorbidity index revised value. Conclusion: Patients with IBD are at increased risk of subsequent ION development. Moreover, for patients with comorbidities, the risk of ION development is significantly higher in those with IBD than in those without.